Improving soil carbon sequestration stability in Siraitia grosvenorii farmland through co-application of rice straw and its biochar - Liu, Xuehui; Yang, Yu; Xie, Yaqi; Zeng, Yicheng; Li, Ke; Hu, Lening (Frontiers in Plant Science, 2024)
Susbtantial agricultural wastes are produced globally which need urgent management policies.To explore the effective utilization of agricultural waste in enhancing soil quality and carbon sequestration capacity, straw and its biochar can be applied as soil ameliorants. This study was designed to investigate the impact of different return-to-field methods of rice straw on the transformation between different carbon components in the soil of Siraitia grosvenorii fields. We hypothesize that rice straw and its biochar, as soil amendments, can influence the transformation and cycling of different carbon components in the soil of S. grosvenorii fields through various return-tofield methods. Rice straw, rice straw biochar, and "rice straw + rice straw biochar" were applied as additives in a 2-year field experiment. The results showed that the field application of rice straw and its biochar increased the content of soil organic carbon, the amount of organic carbon mineralization, particulate organic carbon, mineral-associated organic carbon, dissolved organic carbon, and readily oxidizable organic carbon content, while reducing the content of soil microbial biomass carbon. The combined application of rice straw and biochar in S. grosvenorii cultivation fields had a more significant effect on various soil carbon fractions compared to the use of either rice straw or biochar alone. The co-application of rice straw and its biochar to the soil increased the content of soil organic carbon by 117.4%, enhanced the mineralization of organic carbon by 100.0%, and reduced the content of soil microbial biomass carbon by 61.6%. The metabolic entropy and microbial entropy of rice straw and its biochar mixed application in the field were 5.2 and 0.18 times higher than of the control group, respectively. In summary, the return of rice straw and biochar to the field improves soil structure and the content of recalcitrant organic carbon, providing a habitat for microorganisms, thereby promoting the stability and cycling of soil organic carbon.